2020
DOI: 10.1177/1203475420937963
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Botulinum Toxin Type A in Preventing Postoperative Scars and Improving the Cosmetic Appearance of Scars: A Systematic Review and Meta-Analysis

Abstract: Background Scars with poor cosmesis that develop after wound healing may affect normal life. Objective To assess the efficacy and safety of botulinum toxin type A (BTXA) in preventing postoperative hypertrophic scars or keloids. Methods A systematic review was performed by searching the PubMed, Cochrane Library, and EMBASE databases from their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
6
0
3
Order By: Relevance
“…It has also been proven to be safe and reliable, with reversible side effects. Several trials have suggested that Botulinum Toxin type A can be injected into adjacent musculature around traumatic or incisional wounds (2,(12)(13)(14)(15)(16)(17). The purpose of this clinical trial was to evaluate the effectiveness of BTA using qualitative assessment and quantitative measurements to verify its positive effect on facial scarring.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been proven to be safe and reliable, with reversible side effects. Several trials have suggested that Botulinum Toxin type A can be injected into adjacent musculature around traumatic or incisional wounds (2,(12)(13)(14)(15)(16)(17). The purpose of this clinical trial was to evaluate the effectiveness of BTA using qualitative assessment and quantitative measurements to verify its positive effect on facial scarring.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In the past 2 decades, experimental studies and systematic reviews demonstrated that BTX was effective in minimizing scars. [6][7][8] The wound sites in those previous reports were mainly on the face and neck, and few studies reported on the scar minimizing the effects of botulinum toxin on the trunk, which has a greater tension load than the face.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 2 decades, there have been many experimental studies and meta-analysis of randomized controlled trials demonstrating the ability of botulinum toxin Type A (BTX) to improve the scars' appearance. [6][7][8] Interestingly, previous studies revealed that BTX inhibits fibroblast growth and decreases the expression of a profibrotic cytokine, transforming growth factor-b1. 9 However, most of the scars in previous trials were located on the face and neck area.…”
mentioning
confidence: 99%
“…Todo trauma en la piel trae como consecuencia la generación de una cicatriz, sin embargo, algunos individuos desarrollan tejidos hipertróficos y/o queloides en el proceso de reparación tisular (exceso de fibrosis que no remite, deposición de colágeno excesiva, angiogénesis acelerada) (Austin et al, 2018 ;Bi et al, 2019 ;Yang & Li, 2019 ;Zhang W et al, 2020 ;Fu et al, 2022).…”
Section: Introductionunclassified
“…Este proceso resulta en una parálisis de la musculatura mediante una quimio-inmovilización (Rizo & Südhof, 2002 ;Austin et al, 2018), disminuyendo la tensión en los bordes de la herida en reparación, el cual es un factor crítico en el proceso de cicatrización (Austin et al, 2018 ;Lee & Jang, 2018 ;Bartkowska et al, 2020 ;Chen et al, 2020 ;Guo et al, 2020 ;Song et al, 2020 ;Zhang W et al, 2020 ;Qiao et al, 2021 ;Xu et al, 2021 ;Fu et al, 2022 ;Yue et al, 2022). Adicionalmente, el uso de TB podría tener un efecto profiláctico.…”
Section: Introductionunclassified